Money creation and financial instability: An agent-based credit network approach - Matthias Lengnick; Sebastian Krug; Hans-Werner Wohltmann (Kiel Institute for the World Economy (IfW), 2012)
The authors pick up the standard textbook approach of money creation and develop a simple agent-based alternative. They show that their model is well suited to explain the endogenous creation of money. Although more general, their model still contains the standard results as a limiting case. The authors also uncover a potential instability that is hidden in the standard approach but easily recognized within a strict individual-based and stock-flow consistent version. They show in detail how individual interactions build up systemic risk and how banking crises are triggered by the maturity mismatch of different cash-flows and spread by the depreciation of non-performing loans (e.g. interbank or government debt).
Keywords: E42; E51; C63; G01; 330; financial instability; endogenous money; agent-based macroeconomics; stock-flow consistency; disequilibrium analysis